Socio-Political Organizations in the Central Black Earth Region (1928-1934) - Alexander Yurievich Saran (Управленческое консультирование)
The article analyzes socio-political organizations in the Soviet Union at the regional level at the turn of 1920-1930s on the example of Central Black Earth region and their relationship with the regional authorities. At this critical period the government takes control of/or liquidates these foundations of civil society.